Ley grassland under temperate climate had a legacy effect on soil organic matter quantity, biogeochemical signature and microbial activities. (July 2018) - Crème, A.; Rumpel, C.; Le Roux, X.; Romian, A.; Lan, T.; Chabbi, A.
Abstract: Temporary (ley) grassland introduced into cropping cycles has been advocated as being beneficial for the delivery of ecosystem services by agricultural soils. The management of these temporary grasslands has unknown effects on soil organic matter (SOM) concentrations and biogeochemical properties of the cropland soils following the grassland phase. Here, we investigated the legacy effect of differently managed temporary grasslands, i.e. change of soil properties lasting beyond three years of crop. We assessed soil organic carbon (SOC) quantity and SOM biogeochemical signature (composition of soil neutral carbohydrates and lignin), as well as microbial activities (potential C and N mineralization and denitrification). We used a long-term field experiment on Cambisol with temperate climate in western France, where temporary grassland management practices differed in terms of duration (3 or 6 years) and presence or absence of N fertilisation. Topsoil (10 cm) samples were collected after a 3-yr crop rotation (maize, wheat, barley). Our results showed that N fertilisation during the grassland phase was necessary to maintain soil C and N concentrations beyond three years of crop. Temporary grassland management may affect microbial activities as indicated by contrasting polysaccharide and lignin composition. It had however, no effect on potential CO2 and N2 O emissions during laboratory incubations. The biogeochemical signature of SOM was close to continuous grassland only in treatments with 6 yrs of fertilized temporary grassland. We thus, conclude that the legacy effects of a grassland phase on SOC quantity and properties of SOM depend on its management. Graphical abstract: Image 1 Highlights: Soil organic matter composition in 0–10 cm under grassland was different from that under cropland. Soil organic matter properties can show non-progressive response to temporary grassland duration. Fertilisation of temporary grasslands was necessary to increase SOC concentration.